Optimalisasi Pengelolaan Sarana dan Prasarana sebagai Upaya Peningkatan Kualitas Layanan Pendidikan - Muhammad Ibnu Faruk Fauzi (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2024)
This study aims to analyze the importance of facilities and infrastructure management in supporting the quality of educational services in educational units. In the context of modern education, facilities and infrastructure not only function as technical support for teaching and learning activities, but also as indicators of the quality of educational institutions. This research uses the library research method by examining various scientific sources, both in the form of journals, books, and relevant research reports. The results of the study show that effective management of facilities and infrastructure includes the process of planning, procurement, utilization, maintenance, and continuous evaluation of educational facilities. Each of these stages has an important role in ensuring the availability of a safe, comfortable, and conducive learning environment for all school residents. In addition, transparent and participatory management can increase a sense of responsibility, care, and efficiency in the use of facilities. The management of facilities and infrastructure based on the needs of students and the development of information technology has proven to be able to strengthen the quality of educational services and support the achievement of learning goals optimally. These findings provide practical implications for schools and policymakers to continue to strengthen data-driven educational facilities management systems and cross-stakeholder collaboration.